Design 5.0 µm Gap Aluminium Interdigitated Electrode for Sensitive pH Detection. Issue 1 (May 2020) - Afnan Uda, M.N.; Bahari Jambek, Asral; Hashim, U.; Uda, M.N.A.; Parmin, N.A.; Bakar, A.H.A; Anuar, Aminudin; Bakar, M.A.A.; Sulaiman, M.K.
Abstract: The aim of the research study to design high sensitive biosensor for medical applications. IDE pattern was designed using AutoCAD software with 5 µm ginger gap. The fabrication process was done using a conventional photolithography process and standard CMOS process. The fabricated electrode was physically characterized using a low power microscope (LPM) and a high power microscope (HPM). The electrically validated through I-V measurements and chemically tested with different pH buffer solutions. Al IDE was well fabricated with 0.1 µm tolerance between the design mask and fabricated IDEs. Electrical measurements confirmed that IDE was well fabricated without any shortage and results of similar IDE samples were confirmed that the repeatability of the device. The extremely small current variations in nano ampere range were quantitatively detected using an extra small volume of 2 µl for different pH buffer solutions. It is confirmed that IDEs are sensitive in both alkali and hydroxyl ions medium.